Operação de uma microrrede com geração híbrida oceânica e solar fotovoltaica - ALMEIDA, Jessica de Sousa (2019)
Electric power systems are going under fundamental changes that consist, among other things, in the modernization of generation, transmission and distribution technologies. The electrical generation from large centralized systems, usually based on fossil fuels, began to move to a new ideology that consists in more decentralized systems with small generating units, connected to the conventional electric grid and using alternative sources of energy, the microgrids. The growing integration of distributed generation into power systems, due to the need to meet the demand for electricity, in a reliable and sustainable manner, directs efforts to evaluate the impacts caused by the connection of these with the distribution system as well as the analysis of the optimized operation of these systems which are characterized by the variability of renewable sources. These energy sources are preferred because they are environmental friendly and their integration to form a hybrid system presents an excellent choice for distributed energy production improving the reliability, efficiency and safety of the energy system. This dissertation discusses the operation of a micro-grid with oceanic and solar photovoltaic hybrid generation. Hybrid systems with solar photovoltaic generation have already been well studied due to the fact that this is a consolidated technology. In view of these aspects, this work proposes the study more directed to the oceanic energy integration impacts, which is a renewable source still little studied, in the conventional distribution network. Subsequently, the optimum dispatch problem of an oceanic and solar photovoltaic hybrid microgrid with storage system and connected to the electric grid was formulated and solved. The problem was formulated as a non-linear optimization problem with mixed variables, which is solved efficiently through a problem-oriented metaheuristic.